Endothelin 1 mediates ex vivo coronary vasoconstriction caused by exogenous and endogenous cytokines. - Klemm, P (1995)
Treatment of rats with cytokines has been associated with an increase in the circulating levels of endothelin 1 (ET-1). Here we show that administration of tumor necrosis factor alpha (TNF-alpha; 4 micrograms.kg-1) to anesthetized rats caused within 15 min a strong elevation in the circulating levels of ET-1. This was associated with a striking coronary vasoconstriction in hearts from these animals when they were removed and perfused in vitro by the Langendorff technique. This vasoconstriction was largely overcome by treatment with either the endothelin type A (ETA) receptor antagonist FR 139317 or antibody against ET-1. Furthermore, it was mimicked by in vivo exposure to exogenous ET-1. Endogenously produced TNF-alpha may also cause such a coronary vasoconstriction, for treatment with interleukin 2 (600 micrograms.kg-1) produced an increase in coronary perfusion pressure that correlated with the increases in circulating TNF-alpha. This coronary vasoconstriction was substantially reversed by treatment either with antibody against TNF-alpha or with FR 139317. We suggest, therefore, that cytokine-driven changes in the production of ET-1 are key events in the development of vascular pathologies.